Histochemical characterization of the sialic acid residues in mouse colon mucins. Issue 2 (29th October 2012) - Mastrodonato, Maria; Mentino, Donatella; Liquori, Giuseppa Esterina; Ferri, Domenico
Abstract The mucins of colonic murine mucus are highly O‐glycosilated sulfosialoglycoproteins. We have characterized the sialylation pattern of oligosaccharide chains of colonic murine mucins by conventional histochemical methods and by lectin histochemistry combined with chemical pretreatments and sialidase digestion. Oligosaccharide chains are strongly sulphated, with an increase of sulfation from the proximal toward the distal colon and a decrease of sialic acid expression and acetylation toward the distal colon. In the goblet cells of proximal colon, sialic acid bound α2, 3 to Galβ1, 3GalNAc subterminal dimers is diacetylated at C7, C8;C7, C9;C8, C9 or triacetylated at C7, 8, 9. In the distal colon, sialic acid‐linked α2, 3 to Galβ1, 3GalNAc subterminal dimers shows reduced O‐acetylation at C7 and/or C8, while acetyl substituents at C9 and at C4 are almost absent. Sialic acid is involved in different essential physiological functions; thus, alterations of its expression and acetylation in oligosaccharide chains of intestinal mucins are generally associated with diseases, such as ulcerative colitis and cancer. Mice may represent a suitable animal model to study alterations of oligosaccharidic chains in colonic mucins and lectin histochemistry combined with chemical pretreatments, and enzyme digestion may be a valuable tool for this study. Our present work may represent a landmark for further lectin histochemical studies to evaluate alterations of mouse colon mucins under different physiological, pathological, or experimental conditions, with possible translational value in humans. Microsc. Res. Tech., 2013. © 2012 Wiley Periodicals, Inc.